Paradox of Agrarian Justice in the Relocation of Jragung Dam Residents - Lina Puji Lestari Hamid; Rodiyah (Program magister Kenotariatan Fakultas Hukum Universitas Lambung Mangkurat, 2026)
The construction of the Jragung Dam in Semarang Regency as a National Strategic Project has raised a dilemma between development efficiency and the protection of citizens' rights. Different from the case of other dams such as Cipanas or Jatigede, this study found a major gap in the form of a conflict of authority between the Pemali Juana River Area Center (BBWS) and the local government in the provision of basic relocation facilities, which has an impact on the fulfillment of the community's constitutional right to a healthy environment (Article 28H of the 1945 Constitution). This study uses a juridical-empirical approach with socio-legal analysis to assess the effectiveness of the implementation of Law Number 5 of 1960 and Law Number 2 of 2012. The results of the study show that the compensation mechanism is still administrative and fails to realize the principle of compensation-as-transformation, where relocation should be a means of improving the welfare of residents, not just a relocation of residence. In addition, the unpreparedness of basic infrastructure in the new location shows weak institutional coordination and lack of integration between agrarian law policy and environmental law. This study recommends the establishment of an independent supervisory body in the procurement of PSN land to ensure accountability, as well as post-relocation socio-economic audits to ensure the achievement of substantive justice and social sustainability.